Analisis Public Relations Pariwisata Bali dalam Menjaga Citra Diri - Hamdi Maulana Hasibuan; Nurhanifah Nurhanifah; Jaman Wahidin Harahap; Muhammad Darisal Hasibuan (Prodi Perpustakaan dan Sains Informasi, 2022)
Tourism is something that is considered important for the community and even the government because tourism is one of the alternatives for development and settlement of the country. Tourism is also in terms of encouraging economic growth in Indonesia. Bali which is a strategic area with its charm and beauty makes Bali has a lot of potential in the field of tourism and economic growth in Indonesia. The Bali Tourism and Culture Office certainly has a big role in Bali tourism's self-image so as to encourage high economic growth because it attracts tourists to visit Bali. This research uses qualitative research methods with data analysis techniques through content analysis uploaded in the media, and studies literature from articles, journals and books related to tourism which are then associated with Bali tourism.